OPTIMATION OF THE INCUBATION TIME FOR ENZYMATIC PRODUCTION OF COCONUT OIL USING THE FRUIT’S LATEX OF Carica papaya L - M Chasani; Sri Sutji S (Universitas Gadjah Mada, 2003)
Optimisations of incubation time of the enzymatic coconut oil extraction using Carica papaya's latex have been done. These researches were performed based on completed randomised design with varying incubation time (12, 24, 36 and 48 hours) and 3 % inoculums. Experimental data covered of yield, refractive index, water content, acid number, iodine number and organoleptic parameters and then analysed using t-test and regression analysis. The result showed that coconut oil produced by enzymatic reaction had good quality especially in iodine number parameter compared with conventional extraction. From the statistical analysis, the product by 24 hours incubation had the highest yield and best quality.